Improving the technology startup ecosystem in the Philippines - Dela Cruz, Sheena Domingo; Dayco, Rolando; Cruz, Edison (Quezon City University of the Philippines Diliman, 2013)
The startup ecosystems have been booming in the Philippines. But it is still not at par to the top startup ecosystem in the world, Silicon Valley. There are still many things that the Philippine startup ecosystem can learn from its fellow Asian countries, India and Singapore, in terms of providing a great ecosystem for the startup entrepreneurs.
One of the most successful startup companies to date is the Instagram. Instagram has been introduced only in 2010. It is a photo sharing program which banks on the different social networking sites popularity by allowing users to share their photos after applying digital filters. The product was first launched in the App store to cater to the Apple users, and then expanded their reach to the Android community in 2012. But this company has been recently purchased by Facebook for 1B dollars, a popular social networking sites, in the largest acquisition deal in history. The success of Instagram on its two-year existence is a feat. (Rusli, 2012)
According to Steve Blank, A startup is an organization formed to search for a repeatable and scalable business model (Blank, 2010). Paul Graham, on the other hand, defined startup based on the growth of the organization.
A startup is a company designed to grow fast. Being newly founded does not in itself make a company a startup. Nor is it necessary for a startup to work on technology, or take venture funding, or have some soft of "exit." The only essential thing is growth. Everything else we associate with startups follows from growth. (Graham, 2012)
The definition focus to a wider audience but for the sake of this paper, we would concentrate on technology startups. According to Roger Posadas, technology is the system of knowledge, skills, methods, tools and materials needed to create a new or improved product, process or service in a reproducible way (Posadas, 1996). To be considered a technology startup, an organization must be able to sway away from the existing systems but delve deeper on how they can introduce innovative technologies to the market.
Silicon Valley is known as the haven for technology startups, the probability of hitting success is very high. New York, on the other hand, is competing on this aspect. But for the purpose of this study, the focus would be on the startups in Asia. The Startup Genome identified the top 25 startup ecosystems in the world. It is a collaborative project created to "crack the innovation code and increase the success rate of startups." It is noticeable that few ecosystems identified are from Asia. (Shontell, 2012)
The Top 25 Startup Ecosystems in the world based on the list released by Startup Genomes are : 1. Silicon Valley (San Francisco, Palo Alto, San Jose, Oakland) 2. New York City (NYC, Brooklyn) 3. London 4. Toronto 5. Tel Aviv 6. Los Angeles 7. Singapore 8. Sao Paolo 9. Bangalore 10. Moscow 11. Paris 12. Santiago 13. Seattle 14. Madrid 15. Chicago 16. Vancouver 17. Berlin 18. Boston 19. Austin 20. Mumbai 21. Sydney 22. Melbourne 23. Warsaw 24. Washington, D.C. 25. Montreal
Most of the identified startup ecosystems are based in the United States and Europe, only Singapore (Singapore City) and India (Bangalore and Mumbai) are included in the list from Asia.
With the help of the Global Competitiveness Report 2012-2013, the various factors involving the growth and success of the startup hubs will be discussed. With the benchmarking from the neighbouring Asian countries, Singapore and India, this study will identify the factors involved in the success of the startups in these geographical locations. These success factors are identified to be present in the Philippines, which has government support for entrepreneurs, number of investors and technology incubators, and even monitoring support. From the benchmarking results, these success factors requires further implementation to stack up with the challenge set aside by the technology and the changing market.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: New business enterprises -- Philippines; Technology